Hand, Foot and Mouth Disease Caused by Coxsackievirus A6, Thailand, 2012 - Jiratchaya Puenpa; Thaweesak Chieochansin; Piyada Linsuwanon; Sumeth Korkong; Siwanat Thongkomplew; Preyaporn Vichaiwattana; Apiradee Theamboonlers; Yong Poovorawan (Emerging Infectious Diseases, 2013)
In Thailand, hand, foot, and mouth disease (HFMD) is usually caused by enterovirus 71 or coxsackievirus A16. To determine the cause of a large outbreak of HFMD in Thailand during June–August 2012, we examined patient specimens. Coxsackievirus A6 was the causative agent. To improve prevention and control, causes of HFMD should be monitored.